The Implementation of Ecotourism Principles in the Geger Bintang Matahari (GBM) Protected Forest At Gunung Putri, Lembang, West Bandung Regency - Fauziyyah, Inas Jihan (SABA: Journal of Tourism Research, 2024)
Ecotourism is one type of tourism that is responsible for the environment. The location of this research is Geger Bintang Matahari (GBM) Gunung Putri, which is one of the ecotourism destinations in a protected forest area, located in Lembang, West Bandung Regency, Indonesia. The main objective of this research is to assess the implementation of ecotourism at GBM Gunung Putri Lembang has been in accordance with the principles of ecotourism, which involves the principles of nature-based, sustainability (local participation and benefit), learning, and moral imperative. The research design is descriptive qualitative, with data collection techniques through interviews, observations, and document studies. The results show that tourism management at GBM Gunung Putri is in accordance with the nature-based principle, but it is still not in accordance with the principle of sustainability because it is related to community discomfort with tourism in the area. Meanwhile, the principle of learning is also have not been applied optimally, because the interpretation related to the environment provided by managers to tourists is still limited, as well as the lack of knowledge and awareness of tourists towards the environment. Likewise, the moral imperative principle is still not in accordance with the implementation of ecotourism at GBM Gunung Putri, because environmental education for tourists is still not optimal.